2006
DOI: 10.1038/sj.bjc.6603248
|View full text |Cite
|
Sign up to set email alerts
|

Genetic nurse counsellors can be an acceptable and cost-effective alternative to clinical geneticists for breast cancer risk genetic counselling. Evidence from two parallel randomised controlled equivalence trials

Abstract: This study compared genetic nurse counsellors with standard services for breast cancer genetic risk counselling services in two regional genetics centres, in Grampian region, North East Scotland and in Cardiff, Wales. Women referred for genetic counselling were randomised to an initial genetic counselling appointment with either a genetic nurse counsellor (intervention) or a clinical geneticist (current service, control). Participants completed postal questionnaires before, immediately after the counselling ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…There is a lack of research looking into what aspects of cancer genetic services patients value and how they would like services to be delivered. The only published exceptions are the work of Torrance et al [11] and Wilson et al [12].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is a lack of research looking into what aspects of cancer genetic services patients value and how they would like services to be delivered. The only published exceptions are the work of Torrance et al [11] and Wilson et al [12].…”
Section: Introductionmentioning
confidence: 96%
“…Torrance et al [11] examined patient satisfaction as one of their secondary outcomes in their anxiety equivalence trials examining nurse counsellors as an alternative to consultants as breast cancer genetic counsellors. Patient satisfaction was high for both consultants and nurse counsellors in both the Grampian and Cardiff equivalence trial samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies found few significant differences between alternative service delivery methods. 6,7,9 Further modifications that have been introduced in the protocol-driven system include review of the patient questionnaire by a specialist genetic nurse, to ascertain which cancer diagnoses require confirmation. This process will result in further savings, where the verification of a diagnosis will not alter the management of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…6 Patient access to surveillance, genetic testing and other care usually depends on the outcome of this counselling and risk assessment. 7 It is important that the counselling not only appropriately identifies women at increased genetic risk of breast cancer 8 to ensure appropriate referral for surveillance, but also identifies those women at low risk early, so as to reduce unnecessary anxiety. 9 Cancer risk counselling should also take into account patients' understanding of risk and modifying behaviours associated with cancer risk, emotional concerns, discussion of family communication strategies and potential family reactions.…”
Section: Introductionmentioning
confidence: 99%
“…An example of CMA in genetics is given by Torrance et al [32]. This randomised clinical trial compared genetic nurse counsellors with clinical geneticists for breast cancer risk genetic counselling.…”
Section: Economic Aspects Of Health Technologies and Gene Technologymentioning
confidence: 99%